Food Security in Shambles: Αn Impact from Sri Lanka National Economic Crisis - Manullang, Abel Josafat (HAPSc Policy Briefs Series, 2022)
Sri Lanka, a state in the South Asia region, is now in the middle of a national economic crisis. The crisis has been mainly attributed to the state’s mounting foreign debts along with its inefficient management of the national economy. Apart from the obvious impact the crisis has over the domestic stability of the state, another impact worth noting is one on the state’s food security. The paper aims to provide analysis in answering the questions of how the national economic crisis affects the food security issue and what government policy was responsible for exacerbating the issue. With the use of a qualitative method of analysis, the concept of food security would also be present to better understand the issue. Later, it is explained how the crisis along with the economic state of Sri Lanka inhibits the government’s role to tackle the issue, hence worsening public opinion and the overall food crisis. For the government’s policy that exacerbated the issue, the past decision back in 2021 to ban the import of chemical fertilizers is believed to be it.